Penerapan Prinsip Ekonomi Sirkular Melalui Program Memilah Sampah Menjadi Emas dalam Perspektif Islam: Studi pada Bank Sampah Jekan Mandiri - Muhammad Noor Amin; Itsla Yunisva Aviva; Sofyan Hakim; Muhammad Noor Sayuti (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to analyze the implementation of circular economy principles through the Waste-to-Gold Savings Program at Bank Sampah Jekan Mandiri and its conformity with the principles of tawāzun and hifdz al-bi'ah from the perspective of Islamic economics. This study employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving the management and customers of Bank Sampah Jekan Mandiri. The results show that the Waste-to-Gold Savings Program integrates waste management with gold savings through a partnership with PT Pegadaian and has been joined by 101 customers. The implementation of circular economy principles is reflected in the application of the reduce, reuse, and recycle (3R) aspects, which contribute to waste reduction, increased public awareness, and the creation of economic value from waste. The program is also in line with the principle of tawāzun as it balances economic, social, and environmental aspects, and is consistent with the concept of hifdz al-bi'ah through environmental preservation efforts, as indicated by increased community participation in waste management activities. However, the program faces several challenges, including low public awareness of waste sorting, fluctuations in waste prices, and limited operational facilities.